2019
DOI: 10.5430/jms.v10n2p49
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Pregnancies Among Females Age 15 to 19 in Rwanda: A Secondary Data Analysis of the 2014/2015 Rwanda Demographic and Health Survey (RDHS)

Abstract: Teenage pregnancy is a significant public health problem in developing countries. Due to biological and social factors, teenagers have more negative health outcomes when pregnant. Pregnancy also causes teenagers to drop-out from school, affecting their job opportunities and long-term financial security. As the risk factors for teenage pregnancies are complex and context-specific, effective strategies to reduce teenage pregnancies must be informed by evidence.This study analyzed the data collected by the 2014-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The Rwandan evidence base on adolescents, contraceptive use and services is more extensive, reflecting secondary analyses of Demographic and Health Survey data (Hakizimana et al 2019;Uwizeye et al 2020). A regional comparison of young women's (15-24 years) contraceptive use shows how Rwanda lags significantly behind its neighbours, despite increases in contraceptive use over the last twenty years (Dennis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Rwandan evidence base on adolescents, contraceptive use and services is more extensive, reflecting secondary analyses of Demographic and Health Survey data (Hakizimana et al 2019;Uwizeye et al 2020). A regional comparison of young women's (15-24 years) contraceptive use shows how Rwanda lags significantly behind its neighbours, despite increases in contraceptive use over the last twenty years (Dennis et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The negative view is further amplified by the adolescents' expression of repercussions of adolescent pregnancy on school attendance as expressed in other studies. Moreover, related research has shown that keeping girl child in school is a way of averting adolescent pregnancy and motherhood [ 20 , 33 , 34 ]. The stigma starts form the girl herself to the school community.…”
Section: Discussionmentioning
confidence: 99%
“…This nding further agrees with a study in South Africa that shows that generally African cultures disapprove of adolescent pregnancies [30].The negative view is further ampli ed by the adolescents' expression of repercussions of adolescent pregnancy on school attendance as expressed in other studies. Moreover related research has shown that keeping girl child in school is a way of averting adolescent pregnancy and motherhood [19,31,32]. The stigma starts form the girl herself to the school community.…”
Section: Discussionmentioning
confidence: 99%